Transcription factor 7-like 2 as type-2 diabetes mellitus diagnostic marker in ethnic Minangkabau - Syamsurizal Syamsurizal; Yanwirasti Yanwirasti; Asman Manaf; Jamsari Jamsari; ML Edy Parwanto; Arif Sardi (Universa Medicina, 2014)
BACKGROUND The prevalence of type-2 diabetes mellitus (T2DM) has been increasing rapidly in developed and developing countries. Many new loci associated with T2DM have been uncovered by genetic and genome-wide association studies, eg. the transcription factor 7-like 2 (TCF7L2) gene variant rs7895340 has been associated with type-2 diabetes mellitus. The aim of this research was to find an association between polymorphisms of TCF7L2 gene variant rs7895340 with T2DM in ethnic Minangkabau.